A STAT3 palmitoylation cycle promotes TH17 differentiation and colitis - Zhang, Mingming; Zhou, Lixing; Xu, Yuejie; Yang, Min; Xu, Yilai; Komaniecki, Garrison Paul; Kosciuk, Tatsiana; Chen, Xiao; Lu, Xuan; Zou, Xiaoping; Linder, Maurine E.; Lin, Hening (Nature (London), 2020)
Cysteine palmitoylation (S-palmitoylation) is a reversible post-translational modification that is installed by the DHHC family of palmitoyltransferases and is reversed by several acyl protein thioesterases 1 , 2 . Although thousands of human proteins are known to undergo S-palmitoylation, how this modification is regulated to modulate specific biological functions is poorly understood. Here we report that the key T helper 17 (T H 17) cell differentiation stimulator, STAT3 3 , 4 , is subject to reversible S-palmitoylation on cysteine 108. DHHC7 palmitoylates STAT3 and promotes its membrane recruitment and phosphorylation. Acyl protein thioesterase 2 (APT2, also known as LYPLA2) depalmitoylates phosphorylated STAT3 (p-STAT3) and enables it to translocate to the nucleus. This palmitoylation–depalmitoylation cycle enhances STAT3 activation and promotes T H 17 cell differentiation; perturbation of either palmitoylation or depalmitoylation negatively affects T H 17 cell differentiation. Overactivation of T H 17 cells is associated with several inflammatory diseases, including inflammatory bowel disease (IBD). In a mouse model, pharmacological inhibition of APT2 or knockout of Zdhhc7 —which encodes DHHC7—relieves the symptoms of IBD. Our study reveals not only a potential therapeutic strategy for the treatment of IBD but also a model through which S-palmitoylation regulates cell signalling, which might be broadly applicable for understanding the signalling functions of numerous S-palmitoylation events. The dynamic and reversible S-palmitoylation of the transcription factor STAT3 enhances its activation and promotes the differentiation of T H 17 cells.